Tantangan Terhadap Implementasi Kualitas Layanan Prima dalam Memenuhi Kebutuhan Informasi Pemustaka Studi Kasus: Perpustakaan Universitas Potensi Utama - Rahman, Idzhari; Hermawan, Nanang; Adam, Aisyah Azhar; Syamanta, Arbana; Wahyuni, Linda (Literatify : Trends in Library Developments, 2024)
Excellent service is not only physically related, but there are other factors that influence it. Excellent service is like an abstract form that can be felt, but it is difficult to see or prove. Excellent service is inseparable from customer satisfaction. If the customer is satisfied, then he will come and come again to the library. This has a very positive impact on increasing user visits to the library. In this study, researchers used a method that is qualitative research, field research is field research which has the characteristics of leatherative research. Researchers by collecting information in the field regarding challenges to the implementation of excellent service quality in meeting library users’ information needs Case Study: Main Potential University Library. Universitas Potensi Utama Library has conducted training for librarians in the fields of services, computers, comparative studies to various more advanced libraries, and participated in internships in the fields of library science and information and communication technology in advanced libraries